Long Lasting Sitting Position and Haemostasis - Makris, P E; Louizou, C; Markakis, C; Tsakiris, D A; Mandalaki, T (Thrombosis and Haemostasis, 1986)
Blood coagulation, fibrinolysis and platelet aggregability were assessed in 8 physicians aged 30-40 years, who had travelled nonstop by car from Salonica to Athens (510 km) and returned to Salonica after 48 h of rest and after administration of 1 g of aspirin. At the end of journey A, platelet aggregability was found to be increased (6 out of 8 persons), AT III was decreased by 30% (p <0.001), the FVIIIiC / FVIIIRiAg ratio was decreased (p <0.02) and ELT was prolonged. At the end of journey B the findings were the following: platelet aggregation was not affected, the decrease of AT III was not statistically significant and ELT was significantly shortened (p <0.005).A common finding of both journeys was the increase of platelet counts at the end (p <0.005).The correlation between long lasting sitting and the response of the haemostatic balance is suggested. The influence of aspirin is discussed.
Keywords: Sitting position and haemostasis; Coagulation mechanism; Fibrinolysis